2003
DOI: 10.1093/genetics/164.3.867
|View full text |Cite
|
Sign up to set email alerts
|

Functional Genomics Reveals Relationships Between the Retrovirus-Like Ty1 Element and Its Host Saccharomyces cerevisiae

Abstract: Retroviruses and their relatives, the long terminal repeat (LTR) retrotransposons, carry out complex life cycles within the cells of their hosts. We have exploited a collection of gene deletion mutants developed by the Saccharomyces Genome Deletion Project to perform a functional genomics screen for host factors that influence the retrovirus-like Ty1 element in yeast. A total of 101 genes that presumably influence many different aspects of the Ty1 retrotransposition cycle were identified from our analysis of 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(18 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…Indeed, when we inactivated NUP84 in the original strain transformed with an integrative plasmid carrying the Ty1-his3AI reporter [49,87], we quantified increased retrotransposition levels, in agreement with our data obtained with the chromosomal reporter (S5A and S5B Fig). However, our comparative assays with alternative reporters [48][49][50][51][52] generally indicated that the increased mobility scored in nup mutants (S5A and S5D Fig) was all the less pronounced that the reporter expression and transposition frequency were elevated in WT cells (S5E Fig). This is exemplified by Ty1 reporters under the control of the strong GAL1 promoter [48,51], with which Nup84 complex mutants confirmedly displayed lower transposition frequencies (S5D Fig).…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…Indeed, when we inactivated NUP84 in the original strain transformed with an integrative plasmid carrying the Ty1-his3AI reporter [49,87], we quantified increased retrotransposition levels, in agreement with our data obtained with the chromosomal reporter (S5A and S5B Fig). However, our comparative assays with alternative reporters [48][49][50][51][52] generally indicated that the increased mobility scored in nup mutants (S5A and S5D Fig) was all the less pronounced that the reporter expression and transposition frequency were elevated in WT cells (S5E Fig). This is exemplified by Ty1 reporters under the control of the strong GAL1 promoter [48,51], with which Nup84 complex mutants confirmedly displayed lower transposition frequencies (S5D Fig).…”
Section: Discussionmentioning
confidence: 89%
“…However, our comparative assays with alternative reporters [48][49][50][51][52] generally indicated that the increased mobility scored in nup mutants (S5A and S5D Fig) was all the less pronounced that the reporter expression and transposition frequency were elevated in WT cells (S5E Fig). This is exemplified by Ty1 reporters under the control of the strong GAL1 promoter [48,51], with which Nup84 complex mutants confirmedly displayed lower transposition frequencies (S5D Fig). This could similarly account for the unchanged Ty1 mobility previously scored in nup mutants using a centromeric plasmid-borne Ty1 reporter [52], which led to higher retrotransposition rates in WT cells as compared to our assay performed at 25˚C (S5F Fig) . In this view, the slight increase in retrotransposition that we scored in nup mutants carrying this reporter (S5C Fig) is not inconsistent with the previously described transposition frequencies [52].…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations